IOT BASED VECHICLE LICENSE TRACKING SYSTEM - M. , Sreedhar; Baskar, Radhika (International Journal of Psychosocial Rehabilitation, 2020)
In this examination work, we investigate the vehicle discovery method that can be utilized for traffic observation frameworks. This framework works with the coordination of CCTV cameras for recognizing the vehicles. Beginning advance will consistently be vehicle object discovery. Haar cascades are utilized for the recognition of vehicles in the film. The Viola Jones algorithm is utilized in preparing these course classifiers. We adjust it to discover one of a kind articles in the video by following every vehicle in a chosen district of intrigue. This is one of the quickest strategies to effectively distinguish, track, and tally a vehicle object with precision up to 78 percent.